Comparing the Effect of Repetitive Transcranial Magnetic Stimulation Therapy and Aerobic Exercise as an Add-on Therapy on the Cognitive Function of Patients with Depression - Ikhwan Muhammad; Hening Laswati Putra; Martha Kurnia Kusumawardani; Agustina Konginan; Fazia (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Background: Cognitive disturbances are a major cause of disability in depression. The antidepressant medication effectively improves cognitive function. However, its adverse effect limits its use, so add-on treatment is needed to support its effectiveness. Aim: This study aims to compare the efficacy of aerobic exercise and repetitive transcranial magnetic stimulation (rTMS) as an add-on treatment for improving cognitive function. Material and Methods: Twenty-seven patients with first episodes of moderate and severe depression were recruited from the outpatient psychiatry clinic to join this randomized controlled trial. Participants were allocated to three groups: antidepressant only, antidepressant with add-on aerobic exercise, and antidepressant with add-on rTMS therapy. All participants received 2 weeks of intervention. Cognitive functions were assessed using Montreal Cognitive Assessment (MOCA). Results: No differences were found in baseline characteristic data between groups. Total MOCA score increased after intervention in a group with no add-on treatment (p=0.007), with add-on aerobic exercise (p=0.011), and with add-on rTMS therapy (p=0.017). Hence, there was no between-group difference (p=0.222). The MOCA subtest analysis revealed between-group differences in changes in delayed recall subtest score (p=0.01). The group with add-on rTMS therapy improved better than the group with antidepressants only (p=0.005). Conclusion: The addition of rTMS therapy resulted in better improved delayed recall function than the addition of aerobic exercise or without any add-on treatment. This finding supports the application of rTMS therapy as an add-on treatment to improve the cognitive function of patients with depression.